Musik sebagai Doa: Eksplorasi Metafora pada Musik Taizé di Skolastikat SCJ Yogyakarta - Sabina Stella Vania; Samsul Maarif; Royke B. Koapaha (Graduate School of the Indonesia Institute of the Arts Yogyakarta, 2025)
Tulisan ini mengkaji perwujudan relasi seni dan agama pada musik Taizé. Lebih khusus, membedah komposisi musik Taizé yang mempunyai peran penting dalam memberikan sensasi makna yang lebih dari sekadar melodi, dan memaparkan data terkait cara berdoa musisi yang menggunakan musik sebagai doa. Tulisan ini menggunakan data lapangan yang mencakup observasi partisipatif dan wawancara selama empat bulan pada tahun 2023 di Skolastikat SCJ Yogyakarta. Data dianalisis dengan pendekatan teologi dan musikologis. Hasilnya, musisi melibatkan aspek metaforis dalam memaknai musik sebagai doa. Melalui instrumen dan melodi yang dimainkan yang memiliki peluang dan pengaruh paling dekat untuk difungsikan sebagai doa bagi musisi. Hal tersebut didukung oleh penggunaan non-harmonic tone pada melodi memberikan kesan komposisi musik yang sangat sederhana, tenang dan damai mendengar setiap langkah melodi yang muncul sama seperti sedang berdoa. Selain melodi, ada tekstur musik heterofoni dilakukan dengan pengembangan nada pada teknik arpeggio yang disusun berdasarkan akor nada utama vokal, ada yang mengenai nada utama untuk beberapa birama, dan ada juga yang terdengar multilinier sehingga hal tersebut dapat membantu para musisi untuk berdoa melalui musik. Music as Prayer: Exploration of Music and Metaphor in Taizé Music at Skolastikat SCJ Yogyakarta ABSTRACTThis research examines the unnecessary relationship between art and religion in Taizé music. More specifically, it dissects the musical compositions of Taizé, which have an important role in providing a sensation of meaning that is more than just a melody, and presents data regarding the way musicians who use music as prayer pray. Research uses field data, which includes participant observation and interviews, for 4 months in 2023 at the Skolastikat SCJ Yogyakarta, including data that were analyzed using theological and musicological approaches. As a result, musicians involve metaphorical aspects in interpreting music as prayer. Through the instruments and melodies played have the closest opportunity and influence to function as prayer for musicians. This is supported by using non-harmonic tones in the melody, giving the impression of a straightforward musical composition, calm and peaceful. Hearing every step of the melody that appears is the same as praying. Apart from melodies, there are heterophonic musical textures carried out by developing notes using the arpeggio technique, which are arranged based on chords of the main vocal notes. Some are about the main notes for several bars, and there are also those that sound multinier so that this can help musicians to pray through music.